Selection of Lactic Acid Bacteria (LAB) Origin of Food Fermentation Probiotic Mixed as Candidate for Broiler - Aprisal, Aprisal; Marlida, Yetti; Husmaini, Husmaini; Harnentis, Harnentis (International Journal of Environment, Agriculture and Biotechnology, 2020)
This research aims to looking for 2 candidates from the new probioticlactic acid bacteria fermented food origin. This study uses seven isolates were isolated from whey, cassava, and fish budu. 7 isolates have been tested potential as a producer of glutamic acid but not known as a candidate probiotic petensinya. This study uses a completely randomized design, each repeated 3 times with 5 stages of the research are: 1) Testing capability isolates at low pH (pH 2.5); 2) testing the ability of isolates in bile (0.3 and 0.5%); 3) Viability isolates 4) Testing capability isolates in killing the pathogenic bacteria (Escherichia coli, Staphylococcus aureus and Salmonella enteritidis). The results showed the 7 isolates can be used as a probiotic candidates with the results of the resistance to pH 2.5 for 3 hours is 63.91-92.75% and the 6 hour incubation is 48,76-72.44%, resistance to bile salt concentration of 0.3% showed resistance to 22.86-83.57% and a concentration of 0.5% showed resistance 18.35-72,77%, 81.05-92.67% viability and inhibitory effect on the bacteria Escherichia coli is 7:33 to 12:01 mm, is 11:11 to 14:05 mm Staphylococcus aureus and Salmonella enteritidis is 12:02 to 18:08 mm. From 7 isolates after penseleksian ability as a candidate probiotic mixture then isolate F6 from durian fermented and isolate C8 from buffalo milk fermented (Dadih) are able to live at pH 2.5 for 3 hours of 92.75% and 86.06%, at 6 hours of 72.44 and 71.42%, the bile salt 0.3% were 83.57% and 78.75% and the concentration 0.5% are 77.17% and 72.77%, with viability were 92.67% and 92.23%, while the ability to kill pathogens such as Escherichia coli was 10.49 and 8.89 mm, Staphylococcus aureus was 14.05 and 13.70 mm, dan Salmonella enteritidis was 18.08 and 14.18 mm.